LEGAL PROTECTION AND DETERRENT EFFECT ON BULLYING PERPETRATORS IN INDONESIA - Anggi Putra Dito Harahap; T Riza Zarzani; Abdul Razak Nasution (PT. Sinergi Legal Publisher, 2024)
This study discusses legal protection and deterrent effects on perpetrators of bullying in Indonesia, with a primary focus on bullying committed by children in the school environment. Bullying is a form of physical or psychological violence that can have significant negative impacts on perpetrators and victims. In a legal context, bullying is considered an unlawful act that requires serious attention. This study uses a normative juridical method with a descriptive approach to analyze related laws and regulations, especially the Child Protection Law (Law No. 35 of 2014) and the Juvenile Criminal Justice System (Law No. 11 of 2012). The results of the study indicate that there are various forms of legal protection for child perpetrators, such as the right to diversion to avoid formal trials, as well as other basic rights in accordance with the principles of restorative justice. The deterrent effect on perpetrators can be achieved through the application of criminal sanctions and proportional actions, such as imprisonment as regulated in Article 80 of Law No. 35 of 2014. In addition, diversion as an out-of-court settlement approach is considered effective in reducing the negative impact of the judicial process on children, while encouraging recovery for victims. This study concludes that legal protection and the implementation of diversion for perpetrators of bullying are important steps in creating a just, rehabilitative, and preventive legal system. The recommendations of this study include increasing consistent legal implementation and socialization to the community to reduce the number of bullying among children.